2015
DOI: 10.5901/mjss.2015.v6n4p150
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurial Skill Acquisition and Youth’s Self-Employment in Malaysia: How Far?

Abstract: The objective of this study was to examine the moderating effect of self-motivation on the relationship between entrepreneurial skill acquisition and self-employment practice among graduates from Malaysian public universities. It is a known fact that youth enterprises could generate employment opportunites and lead to economic growth of a country; however, researches have reported that most of entrepreneurship graduates from Malaysian universities do not go into entrepreneurship practice five years after gradu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 15 publications
2
29
0
Order By: Relevance
“…Most of the GLCs are publicly owned and controlled by the Malaysian government thus, large and complex volumes of data and information is typically processed routinely. However, Ekpe et al (2015;2016) argued that the importance of entrepreneurial skills in improving GLC is vital to harness technological advancement. Harris et al (2016) stated that public relations officers are increasingly being required to process immense information before making decisions on how to ensure sustainability, brand, and image of a given GLC organisation.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the GLCs are publicly owned and controlled by the Malaysian government thus, large and complex volumes of data and information is typically processed routinely. However, Ekpe et al (2015;2016) argued that the importance of entrepreneurial skills in improving GLC is vital to harness technological advancement. Harris et al (2016) stated that public relations officers are increasingly being required to process immense information before making decisions on how to ensure sustainability, brand, and image of a given GLC organisation.…”
Section: Introductionmentioning
confidence: 99%
“…Drawing on Technology Acceptance Model, the antecedents of a healthy lifestyle among the citizens of Asian countries were reviewed and research hypotheses were offered. It is recommended that more Asian values such as entrepreneurial skills acquisition [56], [57] and cultural diversity [58] can be moderating variables to advance the conceptual framework theoretically. Finally, recommendations are proffered to various stakeholders on how to improve a healthy lifestyle in Asia.…”
Section: Resultsmentioning
confidence: 99%
“…16, Issue 1 (Feb) 2021 While a study by Omar et al, (2019) on 496 undergraduate students of Universiti Kebangsaan Malaysia (UKM) suggests that entrepreneurial education may be useful in producing high entrepreneurial intentions among students enrolled in higher institutions of education in Malaysia, thus, it can be concluded from the findings that three critical drivers, self-efficacy, the need for independence, and motivation, are significant and are positively associated with entrepreneurial intention, particularly among students at higher institutions of learning. Ekpi and Razak (2015) suggested that skill acquisition, self-motivation, and social influence are other factors that need to be emphasised on top of education support. In addition, Ekpi and Mat (2016) surveyed 319 semester-5 university undergraduate students (student entrepreneurs) during the 2015/2016 academic session from three public universities in Peninsular Malaysia, using stratified proportionate random sampling.…”
Section: The Impact Of Education Support and Entrepreneurial Intentionmentioning
confidence: 99%